Comparative study on batter, quality characteristics and storage stability of muffins using natural ingredients (preservatives) and synthetic preservatives. Issue 6 (17th March 2017) - Soumya, C.; Sudha, M. L.; Vijaykrishnaraj, M.; Negi, Pradeep S.; Prabhasankar, P.
Abstract: Lemon grass (LG) is found to be effective in retarding mould growth. Spices such as clove and cinnamon (CC) have good antioxidant and antimicrobial properties. Muffins were prepared using synthetic (calcium propionate/potassium sorbate) and natural‐preservatives namely LG (0.1, 0.2, and 0.3%), and CC mix in the ratio of 1:1 (CC 1, 2, and 3%). However, addition of natural ingredients/preservatives increased the viscosity of muffin batter from 113, 600 (centipoise, cP) (control) to 124, 000 cP (samples). Sensory evaluation showed that addition of 0.2% LG and 2% CC had acceptable overall quality. Although total aerobic mesophilic count (1.67–2.19 log CFU/g), yeast and mould count (1.13–2.34 log CFU/g) were not much different in all the samples throughout the storage. The visible mould growth was observed on the 24th day of storage in muffins containing either natural or synthetic preservatives. Pathogenic organisms such as Escherichia coli and Salmonella were absent in all the muffins. Practical applications: Lemon grass, clove, and cinnamon can be used as natural preservatives in muffins, and the muffins can be stored up to 24 days without mould growth. However, there is more beneficial health effects for the consumers with naturally added preservatives those who care about the shelf life.